1975
DOI: 10.1037/h0076468
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of pain in childbirth by the alleviation of anxiety during pregnancy.

Abstract: Measures of fear and anxiety were taken before and after courses in childbirth education and childcare for 42 primiparas in the third trimester of pregnancy. A groups X trial analysis of variance indicated that both kinds of instruction significantly reduced two of three pregnancy-related anxieties, namely, Fears for Baby and Irritability and Tension. Only the childbirth education course (Lamaze method) succeeded in reducing general anxiety level, as measured by the IP AT Anxiety Scale. Anxiety level was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…(4,9,10,11,13,39) Maternal fear is reduced by education. (9,20,21,33,49,61,70) PCP would, in this way, also reduce obstetric complications (4,16,1?,18,23,72) and negative birth experiences (32., 47) which are typical results of maternal anxiety.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(4,9,10,11,13,39) Maternal fear is reduced by education. (9,20,21,33,49,61,70) PCP would, in this way, also reduce obstetric complications (4,16,1?,18,23,72) and negative birth experiences (32., 47) which are typical results of maternal anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…A review of the literature found n~~erous references stating that women who are able to (meaning not drugged) and allowed the opportunity of actively participating in childbirth have more fulfilling birth experiences than those who rely on physicians and drugs. (9,11,13,16,20,31,39,69,72) Wlllmuth, Weaver and Borenstein•s research discovered, the technological, scientific approach of today's medicine often fosters the patient's sense of . powerlessness.…”
Section: Effectiveness Of Prenatal Education In Reducing Obstetric 9omentioning
confidence: 99%
See 2 more Smart Citations
“…Many women also begin to experience concern over the coming dissociation from the child [Arbeit, 1975;Bibring et al, 1961Bibring et al, , 1976Blum, 1980;Lukesch, 1981], Much research suggests that as the event approaches, birth anxiety and the expectation of pain becomes dominant [Lubin et al, 1978;McDonald, 1963], In addition to the fear of pain, women also indicate fear of loss of self-control, helplessness within the anonymous setting of the hospital, deforma tion of the child, and post-partum experiences [Lukesch. 1981 ;Seeman, 1981], Several stud ies have identified a positive relationship be tween level of anxiety and drug consumption, emotional problems, obstetrical medication during labour, and complication of birth [Brackbill, 1979;Klusman, 1975;Lukesch and Lukesch. 1976;Yangctal., 1976].…”
Section: Anticipation and Preparationmentioning
confidence: 99%